Boundary layer drag reduction research hypotheses derived from bio-inspired surface and recent advanced applications. (December 2015) - Luo, Yuehao; Yuan, Lu; Li, Jianhua; Wang, Jianshe
Abstract: Nature has supplied the inexhaustible resources for mankind, and at the same time, it has also progressively developed into the school for scientists and engineers. Through more than four billions years of rigorous and stringent evolution, different creatures in nature gradually exhibit their own special and fascinating biological functional surfaces. For example, sharkskin has the potential drag-reducing effect in turbulence, lotus leaf possesses the self-cleaning and anti-foiling function, gecko feet have the controllable super-adhesion surfaces, the flexible skin of dolphin can accelerate its swimming velocity. Great profits of applying biological functional surfaces in daily life, industry, transportation and agriculture have been achieved so far, and much attention from all over the world has been attracted and focused on this field. In this overview, the bio-inspired drag-reducing mechanism derived from sharkskin is explained and explored comprehensively from different aspects, and then the main applications in different fluid engineering are demonstrated in brief. This overview will inevitably improve the comprehension of the drag reduction mechanism of sharkskin surface and better understand the recent applications in fluid engineering.